Contextualisation of Sufi spirituality in seventeenth- and eighteenth-century China : the role of Liu Zhi 1662-1730 - Lee, David (Cambridge, United Kingdom : James Clarke & Co, 2016)
A significant study of the writings of the Chinese Muslim scholar Liu Zhi and his innovative role in contextualising Islamic texts for a Chinese cultural audience. Includes translations of some of his key works.
Includes bibliographical references.
Vendor-supplied metadata.
Master record variable field(s) change: 050, 072
Keywords: Liu, Jielian, -- active 1670-1724.; Liu, Jielian, -- active 1670-1724.; Sufism -- China -- History -- 17th century; Sufism -- China -- History -- 18th century; Sufism; China; RELIGION / Islam / General; RELIGION / Islam / Sufi; 1600-1799; Electronic books; History